2021
DOI: 10.1590/0103-8478cr20200979
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in essential oil content and chemical profile of mint in southeast of Brazil

Abstract: This study evaluated the influence of seasonality in essential oil (EO) chemical composition of Mentha x piperita L. and Mentha viridis L. grown in southeast of Brazil. Leaves were collected from November 2011 until August 2013, in the middle of the following seasons: Spring (November), Summer (February), Autumn (May) and Winter (August). EO extraction was carried out by hydrodistillation in Clevenger apparatus for 1 hour. Chemical composition of EO was analyzed by GC-FID and GC-MS. The EO content and its chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Once a plant's composition changes, its biological activity can also change. [6] Hence, this is an essential subject that needs to be assessed for EO production and its application. Recent studies have demonstrated the seasonal influences on the biosynthesis and chemical composition of EO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once a plant's composition changes, its biological activity can also change. [6] Hence, this is an essential subject that needs to be assessed for EO production and its application. Recent studies have demonstrated the seasonal influences on the biosynthesis and chemical composition of EO.…”
Section: Introductionmentioning
confidence: 99%
“…When working with medicinal plants, it is important to know that the EO chemical composition can change significantly due to different variables, such as environmental conditions and plant phenology. Once a plant's composition changes, its biological activity can also change [6] . Hence, this is an essential subject that needs to be assessed for EO production and its application.…”
Section: Introductionmentioning
confidence: 99%
“…EO are industrially important natural products of aromatic plants [ 23 ]. It is well known that EO yield significantly varies with the season [ 24 , 25 , 26 ]. Indian blackberry leaf EO was obtained during winter and spring seasons.…”
Section: Resultsmentioning
confidence: 99%
“…Studies conducted on various plant species have shown that the accumulation of specialised metabolites depends on various environmental factors, including temperature, light, and soil moisture [14]. In the higher plant studied so far, such as Thymus [15], Rosmarinus [16,17], Helichrysum [18], Mentha [19], and Eugenia patrisii [20], variability in quantity or composition of essential oil content related to the season or different environmental conditions has also been demonstrated. Similarly, seasonal changes in the composition of volatile organic compounds (VOCs) were observed in one of the species of the genus Calypogeia, that is, in the previously analysed Calypogeia azurea [21].…”
Section: Introductionmentioning
confidence: 99%